The effect of different treatment protocols on shear bond strength in resin composite restoration repair - Ayşenur Bulut; Oya Bala; Sinem Akgül (BMC, 2024)
Abstract Background It was aimed to investigate the effect of sandblasting and laser surface treatment on shear bond strength in composite restoration repair in vitro. Methods A micro-hybrid composite (Filtek Z250, 3 M-ESPE, USA) was used to prepare 120 samples. The samples were subjected to a thermal cycle test 5,000 times between 5 and 55 0C, and they were randomly divided into 12 groups (n = 10). No surface treatment was performed in Groups 1 to 4, which were designed as control groups. The surfaces of the samples in Groups 5 to 8 were sandblasted with a Cojet device, and the surfaces of the samples in Groups 9 to 12 were applied Er, Cr: YSGG laser. After the sample surfaces were divided into groups with and without acid etching, universal adhesive was applied, and the repair process was performed using Filtek Z250 or nano-filled resin composite (Filtek Ultimate, 3 M-ESPE, USA). The thermal cycle test was repeated 5,000 times between 5 and 55 0C on all repaired samples. The repair shear bond strength of the samples was measured using a universal testing device (Shimadzu IG-IS, Kyoto, Japan). The fracture types were evaluated by optical microscopy and scanning electron microscopy (SEM). Statistical analyses of the findings were evaluated by the Kruskal Wallis test and Mann Whitney U test at 0.05 significance degree. Results The highest mean shear bond strength values were obtained from the samples sandblasted with CoJet, followed by Er, Cr: YSGG laser, and the control group. It was determined that there was a significant difference between the mean shear bond strength values obtained from the control group and the other surface treatment groups (p < 0.05). In general, significantly higher mean shear bond strength values were obtained when the universal adhesive was applied in total-etch mode compared to the application in self-etch mode (p < 0.05). Additionally, it was determined that higher shear bond strength values were obtained with Filtek Ultimate compared to Filtek Z250 (p < 0.05). Conclusion Within the limitations of this study, it can be concluded that the use of universal adhesive in total-etch mode, in addition to surface treatments on the resin composite surface in the repair protocol and the use of nano-filled resin composite as repair material can increase the mean shear bond values in repair.